THE EFFECT OF SMOOTH MUSCLE ON THE INTERCELLULAR SPACES IN TOAD URINARY BLADDER - DiBona, Donald R. (The Rockefeller University Press, 1970)
Phase microscopy of toad urinary bladder has demonstrated that vasopressin can cause an enlargement of the epithelial intercellular spaces under conditions of no net transfer of water or sodium. The suggestion that this phenomenon is linked to the hormone's action as a smooth muscle relaxant has been tested and verified with the use of other agents effecting smooth muscle: atropine and adenine compounds (relaxants), K(+) and acetylcholine (contractants). Furthermore, it was possible to reduce the size and number of intercellular spaces, relative to a control, while increasing the rate of osmotic water flow. A method for quantifying these results has been developed and shows that they are, indeed, significant. It is concluded, therefore, that the configuration of intercellular spaces is not a reliable index of water flow across this epithelium and that such a morphologic-physiologic relationship is tenuous in any epithelium supported by a submucosa rich in smooth muscle.